Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Ulang Air Minum Dalam Kemasan (AMDK) Merek Club di Kota Mataram - Afriza Ade Ningsih; Hilmiati (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to determine the influence of Product Quality and Price on the Interest in Repurchasing Bottled Drinking Water (AMDK) Club Brands. The type of research used is causal associative research with a quantitative approach. The population in this study is the people of Mataram City with a sample of 100 respondents. The data collection techniques used are survey and questionnaire approaches in the form of questionnaires containing statements about interest in repurchases, product quality and price. Data processing in this study uses SPSS 23, where research instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis tests are carried out. Based on the results of the data analysis, it shows that: (1) Product quality has a positive effect on the interest in repurchasing Club brand AMD. (2) The price has a negative effect on the interest in repurchasing Club brand bottled water.